2021
DOI: 10.5194/acp-21-6781-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Balloon-borne in situ profiling of Saharan dust over Cyprus with the UCASS optical particle counter

Abstract: Abstract. This paper presents measurements of mineral dust concentration in the diameter range from 0.4 to 14.0 µm with a novel balloon-borne optical particle counter, the Universal Cloud and Aerosol Sounding System (UCASS). The balloon launches were coordinated with ground-based active and passive remote-sensing observations and airborne in situ measurements with a research aircraft during a Saharan dust outbreak over Cyprus from 20 to 23 April 2017. The aerosol optical depth at 500 nm reached values up to 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…The PNC in the desert area was approximately 1/10th of that in the urban area, whereas R eff and Cv were larger than the values observed by urban UAV and mobile monitoring. In addition, R eff was similar to observations in desert and forest land; however, the PNC varied greatly [37,52,53].…”
Section: Comparison With Previous Studiessupporting
confidence: 76%
See 2 more Smart Citations
“…The PNC in the desert area was approximately 1/10th of that in the urban area, whereas R eff and Cv were larger than the values observed by urban UAV and mobile monitoring. In addition, R eff was similar to observations in desert and forest land; however, the PNC varied greatly [37,52,53].…”
Section: Comparison With Previous Studiessupporting
confidence: 76%
“…Some relevant studies were reviewed for comparison with previous observations. As listed in Table 3, only a few studies have addressed these parameters based on UAV, and large differences exist between the values obtained from observations of different land types [34,37,52,53]. The particle size range of the instrument carried by Weinzierl during UAV observations in the Sahara Desert was similar to that in this study.…”
Section: Comparison With Previous Studiessupporting
confidence: 69%
See 1 more Smart Citation
“…Renard et al (2018) frequently observed particles sized larger than 40 μm at concentrations above 10 -4 cm -3 at a distance from source regions. Other instruments, such as the Universal Cloud and Aerosol Sounding System (UCASS, Smith et al, 2019), a lightweight OPC which can be deployed on radiosondes, dropsondes or UAVs to measure size distributions between optical diameters between 0.4 to 17 μm have also been developed and show promising results (Kezoudi et al, 2021a(Kezoudi et al, , 2021b.…”
Section: Observations From Unmanned Aerial Vehicles Radiosondes and F...mentioning
confidence: 99%